2011
DOI: 10.1007/s10800-011-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple two-step electrochemical synthesis of graphene sheets film on the ITO electrode as supercapacitors

Abstract: In this study, a simple and controllable two-step electrochemical process is described for the synthesis of graphene sheets (GS) film on a cleaned indium tin oxide (ITO) sheet electrode. Namely, the main procedures involve the electrophoretic deposition (EPD) of graphene oxide (GO) film onto ITO electrode and the subsequent in situ electrochemical reduction (ECR) of GO to generate GS film. X-ray photoelectron spectroscopy (XPS) measurement demonstrates that most of the oxygen-containing functional groups in GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 23 publications
2
34
0
1
Order By: Relevance
“…1a system for 20 s [15][16][17]. Thereafter, GO/CF was obtained by freezedrying to form a 3D structure of GO.…”
Section: Resultsmentioning
confidence: 99%
“…1a system for 20 s [15][16][17]. Thereafter, GO/CF was obtained by freezedrying to form a 3D structure of GO.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, several studies [8,30,68,150,166] have reported that post-EPD reduction or thermal annealing of GRM films leads to compaction, surface smoothing and decrease of the interlayer spacing of the deposited GRM films and fibres through removal of trapped water molecules and/or oxygen-containing functional groups. Formation of crevices [96], protruding GRM sheets edges [77,145], and flaky surfaces [153] have been also reported as the result of post-EPD treatment. On the other hand, some studies [77,106] have not observed significant microstructural changes after post-EPD treatment of GRM films.…”
Section: Effects Of Post-epd Treatmentmentioning
confidence: 95%
“…Formation of crevices [96], protruding GRM sheets edges [77,145], and flaky surfaces [153] have been also reported as the result of post-EPD treatment. On the other hand, some studies [77,106] have not observed significant microstructural changes after post-EPD treatment of GRM films. For example, Akhavan et al [106] reported that post-EPD reduction of GRM films with vertically aligned sheets does not alter the films' microstructure.…”
Section: Effects Of Post-epd Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…The second step involves deposition of the colloidal particles on the electrode surface to form a uniform film. EPD has proven useful in many applications such as the assembly of nanoparticles to form nanoparticle films [23][24][25] solid oxide fuel cell (SOFC) fabrication [26], hybrid material synthesis [27], and graphene oxide [28].…”
Section: Introductionmentioning
confidence: 99%